Gasotransmitters in vascular complications of diabetes - Born, Joost C. van den; Hammes, Hans-Peter; Greffrath, Wolfgang (Diabetes, 2016)
In the past decades three gaseous signaling molecules - so-called gasotransmitters - have been identified: nitric oxide (NO), carbon monoxide (CO), and hydrogen sulfide (H2S). These gasotransmitters are endogenously produced by different enzymes in various cell types and play an important role in physiology and disease. Despite their specific functions, all gasotransmitters share the capacity to reduce oxidative stress, induce angiogenesis, and promote vasorelaxation. In patients with diabetes, a lower bioavailability of the different gasotransmitters is observed when compared with healthy individuals. As yet, it is unknown whether this reduction precedes or results from diabetes. The increased risk for vascular disease in patients with diabetes, in combination with the extensive clinical, financial, and societal burden, calls for action to either prevent or improve the treatment of vascular complications. In this Perspective, we present a concise overview of the current data on the bioavailability of gasotransmitters in diabetes and their potential role in the development and progression of diabetes-associated microvascular (retinopathy, neuropathy, and nephropathy) and macrovascular (cerebrovascular, coronary artery, and peripheral arterial diseases) complications. Gasotransmitters appear to have both inhibitory and stimulatory effects in the course of vascular disease development. This Perspective concludes with a discussion on gasotransmitter-based interventions as a therapeutic option.
Gesehen am 08.02.2019